Long term outcomes of total humeral replacement for oncological reconstructions: A single institution experience. Issue 4 (29th June 2020) - Bernthal, Nicholas M.; Upfill‐Brown, Alexander; Burke, Zachary D. C.; Greig, Danielle; Hwang, Richard; Crawford, Brooke; Eckardt, Jeffrey J.
Abstract: Background: There is a paucity of data on long‐term survivorship and outcomes for total humerus replacements (THR) with only two series reporting 10‐year survival. Patients and Methods: A review of 769 consecutive, prospectively collected endoprosthetic reconstructions for oncological diagnoses at a single‐center between 1980 and 2019 was performed. Patients with THRs were isolated and analyzed for outcomes, complications, and modes of failure. Results: Eighteen patients with 20 THR implants were identified. The median follow‐up for surviving patients was 148 months (interquartile range [IQR] = 74‐194) and 60 months (IQR = 17‐155 months) for all patients. Two prostheses required revision for failure, both for symptomatic shoulder dislocation. There were three local recurrences. Revision‐free survival at 5, 10, and 15 years was 100%, 86% and 86%, respectively. There were no cases of ulnar component failure, radial nerve palsy, or periprosthetic infection. Conclusions: THR prosthesis survivorship is comparable to the previous series, with a longer follow‐up than has previously been reported. Symptomatic shoulder instability was common (25%), and was the only cause of revision. Reverse total shoulder could be an important way to address this in the future. Local recurrence rates were high, as has been reported elsewhere for THR.